Eco-friendly pest management in integrated rice-fish farming systems using plant-derived biopesticides to promote sustainable agriculture - Wiratno ,; I.M. Trisawa; I. Taufik; I. Ardi; L. Thesiana; E. Kusrini; D. Susanti; E.W. Minarni; A. Nurawan; A. Jufri; Sukamto ,; Y. Apriyana; et al. (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Integrated rice–fish farming (Minapadi) enhances agricultural sustainability but remains challenged by pest management practices that often rely on environmentally harmful synthetic insecticides. This study aims to develop and assess an eco-friendly pest control strategy using botanical insecticides, ensuring safe integration of rice and fish farming while maintaining ecological balance and improving profitability.METHODS: Field experiments were conducted in Central Java, Indonesia, with four treatments: conventional rice monoculture, Minapadi without insecticide, Minapadi with synthetic insecticides, and Minapadi with botanical insecticides (eugenol-based). Key parameters including arthropod biodiversity, pest incidence, fish survival, rice yield, and economic feasibility were monitored over two planting seasons.FINDINGS: Results showed that Botanical insecticide treatment enhanced arthropod diversity (11 morphospecies versus 9 under synthetic treatments) while effectively reducing pest damage (less than 1 percent caterpillar damage, less than 5 percent grasshopper infestation). No insecticide residues were found in fish, soil, or water samples. Fish survival remained high (more than 90 percent), and rice yields increased by 15 percent compared to conventional practices. Economically, botanical Minapadi systems improved farmers’ net income by approximately 16 percent per hectare.CONCLUSION: The botanical insecticide–based Minapadi system offers a sustainable, eco-friendly approach to managing pests by leveraging plant-derived compounds that biodegrade rapidly and pose minimal risk to non-target organisms, including fish and beneficial arthropods. By integrating these biopesticides into rice–fish farming, we observed not only effective suppression of key rice pests, but also enhanced water and soil quality, leading to healthier fish populations and increased overall system resilience. Economically, the slightly higher input costs of botanical sprays were offset by improved rice yields, reduced post-harvest losses, and higher fish survival rates, resulting in significant gains in net farm income. Taken together, these findings underscore the potential for wider adoption of environmentally sustainable rice–fish integration, contributing to the twin goals of sustainable agriculture and regional food security while offering a scalable model for smallholder farmers.